Real-world PP attachment disambiguation dataset - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains a German dataset for real-world PP attachment disambiguation. The creation, analysis and experiment results of the dataset are described in the paper: Do and Rehbein (2020). "Parsers Know Best: German PP Attachment Revisited"
Produktionsdatum: 2020
Gesehen am 22.11.2023
Keywords: Forschungsdaten; Datenbank